THE RELATIONSHIP OF PROMOTION AND SERVICES WITH INSURANCE POLICY PURCHASE DECISION AT PT. KRESNA RATAMA TUGU, BENGKULU - Roni Nofirdaus; Ida Anggriani; Rina Trisna Yanti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
The purpose of this study is to find out the relationship of promotion with the purchase decision of insurance policy at PT.Tugu Kresna Pratama Bengkulu and to find out the relationship of services with the purchase decision insurance policy at PT. Tugu Kresna Pratama Bengkulu. The analytical method used is Spearman rank correlation and hypothesis testing. Based on the calculation of the Spearman rank correlation coefficient, the calculated value of rho (p) between the relationship between promotion and the purchase decision insurance policy at PT. Tugu Kresna Pratama Bengkulu is 0.877 located at Interpretation interval correlation 0.800-1.000, and the calculated value of rho (p) between the relationship between service with the purchase decision insurance policy at PT. Tugu Kresna Pratama Bengkulu is 0.836 located at Interpretation interval correlation 0.800-1.000. Hypothesis testing between promotion and the purchase decision of insurance policy at PT. Tugu Kresna Pratama Bengkulu is a calculated rho value greater than rho table (0.877> 1,692) and hypothesis testing between service with the purchase decision of insurance policy at PT. Tugu Kresna Pratama Bengkulu is a calculated rho value greater than rho table (0.836> 1,692) so Ho is rejected and Ha is accepted, meaning that there is a significant relationship between promotion and service with the purchase decision insurance policy at PT. Tugu Kresna Pratama Bengkulu.